PENGARUH BRAND IMAGE, RELATIONSHIP MARKETING DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - Syafira Laeluqyana Devandri; Bayu Wijayantini; Wahyu Eko Setianingsih (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the effect of brand image, relationship marketing and celebrity endorser on wardah cosmetic product purchase decisions at Muhammadiyah University of Jember. This type of research is causal quantitative research, using data collection is a purposive sampling questionnaire with a sample of 150 students of S1 Active Wardah consumers at the Muhammadiyah University of Jember. The analytical tool used in this research is multiple linear regression analysis. The results of this study indicate that Brand Image, Relationship Marketing and Celebrity Endorser have a positive and significant effect on purchasing decisions for active undergraduate students at the University of Muhammadiyah Jember.